Implementation status, drivers and barriers to the sick children quality of care improving interventions in the Oromia region, Ethiopia: case study design - Dawit Wolde Daka; Muluemebet Abera Wordofa; Mirkuzie Woldie (BMC Health Services Research)
Abstract Background Improving quality of sick child care is the primary aim of Integrated Community Case Management services and implementation fidelity is critical to translating an evidence-based intervention to practice. A community-based complex intervention was implemented at the health posts of four agrarian regions of Ethiopia from 2017 to 2018 to improve the coverage and utilization of quality child health services. This study aimed to examine the implementation status of child health care quality improvement interventions in program areas of Oromia region, Ethiopia. Methods A case study design using quantitative and qualitative research methods was conducted from September to October 2018. Implementation data were collected using observations, document reviews, and program staff interviews. Program staffs including health extension workers and their supervisors were included in surveys, and purposefully selected key informants from health posts to zonal health office level were included in the qualitative component of the research. The analysis framework was focused on the fidelity of the interventions’ content, frequency, duration, and coverage, as well as the potential moderating factors of implementation using the model proposed by Carroll et al. conceptual framework for implementation fidelity. Results Performance Review Clinical Mentoring was implemented according to the plan (every 6 months) in all of the districts and around nine in ten (88%) of the core contents were implemented. Though mentoring was provided by trained mentors, the duration of mentoring was less than the plan to fully implement all of the core activities. Overall, the mentoring program has reached 88% of health extension workers. Slightly greater than three-fourths of health extension workers have been supervised (76%) according to the plan and 80% of health posts were supplied with required iCCM medicines regularly. Staff turnover, topographical challenges, lack of transportation, competing priorities, weak support and feedback from the District health office, and security problems were frequently mentioned challenges to implementation. Whereas, the existence of continual partner support, the presence of integration and coordination of activities, and changes observed were the facilitators of implementation. Conclusions The implementation status of the Performance Review Clinical Mentoring Meeting was sufficient, while moderate adherence was observed in supportive supervision and supply of medicines. All of the providers were reached with sick children management training. Therefore, the implementation of community-based interventions should be aware of operational challenges in order to improve and sustain the program’s performance.